Targeted therapy in the treatment of malignant gliomas - Rimas V Lukas (OncoTargets and Therapy, 2009)
Rimas V Lukas1, Adrienne Boire2, M Kelly Nicholas1,2 1Department of Neurology; 2Department of Medicine, University of Chicago, Chicago, IL, USAAbstract: Malignant gliomas are invasive tumors with the potential to progress through current available therapies. These tumors are characterized by a number of abnormalities in molecular signaling that play roles in tumorigenesis, spread, and survival. These pathways are being actively investigated in both the pre-clinical and clinical settings as potential targets in the treatment of malignant gliomas. We will review many of the therapies that target the cancer cell, including the epidermal growth factor receptor, mammalian target of rapamycin, histone deacetylase, and farnesyl transferase. In addition, we will discuss strategies that target the extracellular matrix in which these cells reside as well as angiogenesis, a process emerging as central to tumor development and growth. Finally, we will briefly touch on the role of neural stem cells as both potential targets as well as delivery vectors for other therapies. Interdependence between these varied pathways, both in maintaining health and in causing disease, is clear. Thus, attempts to easily classify some targeted therapies are problematic.Keywords: glioma, EGFR, mTOR, HDAC, Ras, angiogenesis